Direito como sistema adaptativo complexo na sociedade digital - Pinho, Ruy Veridiano Patu Rebello (2024)
This is a thesis presenting a theory to interpret and understand Law in its dynamic organicity as a complex adaptive system. To this end, the metatheory of complex systems and their developments in different fields of knowledge are presented, as well as added insights resulting from the thinking of economists, sociologists, administrators and political scientists who produced compatible theories. Complex systems, in the theoretical field, collaborate in a great interdisciplinary synthesis of knowledge. Next, developments of the theory in the field of Law are presented, and a method is proposed for creating models of the legal Complex Adaptive System